Rapid detection of infectious laryngotracheitis virus by standardization of polymerase chain reaction targeting a relatively conserved region of the thymidine kinase gene (University Journal of Zoology, Rajshahi University, 2012)
Infectious laryngotracheitis is an acute upper respiratory tract infection of chickens caused by infectious laryngotracheitis virus. The study was conducted to standardize the polymerase chain reaction targeting a relatively conserved region of the thymidine kinase gene for the rapid detection of infectious laryngotracheitis virus. The vaccine samples were collected from two renowned company of Bangladesh. DNA was extracted from diluted vaccine samples by using Wizard® Genomic DNA purification kit and thymidine kinase gene was amplified by using PCR system 9600 Thermocycler. Two vaccine samples were positively amplified by polymerase chain reaction. A procedure was developed for rapid detection of infectious laryngotracheitis virus by polymerase chain reaction of the conserved region of viral thymidine kinase gene containing DNA fragments. The results obtained in this study suggested that the polymerase chain reaction procedure could serve as a fast and sensitive method for the detection of vaccine strains of infectious laryngotracheitis viruses.   Key words: Infectious laryngotracheitis virus; viral thymidine kinase (TK) gene; polymerase chain reaction DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9468 UJZRU 2010; 29(1): 61-64